Heart rate recovery after exercise as a prognostic predictor in patients with atrial fibrillation. (25th November 2020) - Kato, Y; Itahashi, N; Uejima, T; Semba, H; Arita, T; Yagi, N; Suzuki, S; Otsuka, T; Kishi, M; Kanou, H; Matsuno, S; Oikawa, Y; et al.
Abstract: Background: A delayed heart rate recovery (HRR) after exercise is related to mortality in sinus rhythm. This study aimed to investigate this concept can be applied to patients with atrial fibrillation (AF). Methods: We analyzed 483 patients with AF (mean 65 years, male 74%). HRR integral was calculated by integrating the difference in HR in every 3 second between the end of exercise and the specified time after the exercise (30, 60, 120 and 180 seconds). After evaluating the prognostic power of each HRR integral, we selected HRR integral of 180 seconds (180HRR-integral). Results: We divided the patients into two groups using median value of 180HRR-integral. All-cause mortality, the incidence of cardiovascular events and heart failure events were higher in the poor 180HRR-integral. After adjustment for covariates, the impact of the high 180HRR-integral for all-cause mortality was 3.15 (p=0.057), 1.77 for cardiovascular events (p=0.067) and 1.28 for heart failure events (p=0.519). Conclusion: Poor HRR was associated with worse prognosis in patients with AF. Funding Acknowledgement: Type of funding source: None